Carotid artery stenting (Swiss Medical Weekly, 2012)
Atherosclerotic narrowing (stenosis) of the internal carotid artery accounts for about 10–15% of ischaemic strokes. Carotid endarterectomy (CEA) reduces the risk of stroke in patients with symptomatic stenosis and – to a lesser degree – with asymptomatic carotid stenosis. Endovascular treatment including balloon angioplasty and carotid artery stenting (CAS) has emerged as an alternative to CEA to treat carotid stenosis. The present review summarises the existing evidence on risks and benefits of CAS in comparison with CEA, with a focus on evidence from randomised clinical trials. Across all randomised trials, CEA was associated with a lower risk of peri-procedural stroke or death than CAS, while CAS had lower risks of myocardial infarction, cranial nerve palsy and access site haematoma. The increased stroke risk with CAS is mainly observed in elderly patients; therefore, CAS appears to be a safe option to CEA in younger patients. In the first few years following treatment, both procedures are equally effective in preventing ipsilateral recurrent strokes. Nevertheless, long-term follow-up of ongoing trials must be awaited to investigate whether a potential increase in recurrent stenosis following CAS might limit the long-term effectiveness in stroke prevention. The optimal treatment for asymptomatic carotid stenosis remains to be determined in ongoing clinical trials.